Fabrication of a highly stretchable cellulose with internally and externally dual-plasticized structure. (5th January 2022) - Lee, Woojin; Chung, Jae Woo; Kwak, Seung-Yeop
Graphical abstract: The internally- and externally-plasticized (i.e., dually-plasticized) cellulosic material bearing an alkyl-branched polydecalactone-grafted cellulose and a hyperbranched polycaprolactone can provide an enhanced plasticization behavior with a highly improved stretchability. Highlights: The plasticized cellulose films were prepared by the dual-plasticization method. Combination of cellulose copolymer and hyperbranched plasticizer improved strain. The mechanical properties were critically affected by the structural homogeneity. The dually-plasticized cellulose films exhibited better thermal stabilities. Abstract: In this study, we developed a highly stretchable internally- and externally-plasticized (i.e., dually-plasticized) cellulose, which is composed of a polydecalactone (PDL)-grafted cellulose copolymer (CgPD) and a hyperbranched polycaprolactone (PCL) external plasticizer (HPC). To investigate the effect of molecular structure of PCL external plasticizers on the plasticization behavior of dually-plasticized celluloses, a linear PCL (LPC) and a star-shaped PCL (SPC) were prepared as control groups. It is observed that specific molecular interactions existed between CgPD and external plasticizers in the dually-plasticized celluloses (i.e., CgPD_LPC, CgPD_SPC, and CgPD_HPC, respectively). Especially, CgPD_HPC exhibited the lowest apparent activation energy ( E a = ∼128.8 kJ mol −1 ) required to achieve the plasticizing behavior, which resulted in an enhanced ductility (ε = ∼136%) compared to those of the CgPD (ε = ∼75%), whereas CgPD_LPC and CgPD_SPC displayed severely deteriorated values (ε = ∼25 and ∼59%, respectively). In addition, the dually-plasticized cellulose bearing bulkier HPC exhibited further improved stretchability. These results comprehensively indicate that the highly-branched flexible segments of external plasticizer and structural uniformity induced by effective specific interactions between the plasticizing components play crucial roles in improving plasticization abilities of the dually-plasticized cellulose.